Tinnitus, depression, and suicidal ideation in adults: A nationally representative general population sample. (March 2018) - Han, Kyu-Man; Ko, Young-Hoon; Shin, Cheolmin; Lee, Jae-Hon; Choi, June; Kwon, Do-Young; Yoon, Ho-Kyoung; Han, Changsu; Kim, Yong-Ku
Abstract: Tinnitus is strongly associated with psychiatric symptoms, including depression and suicidality. We aimed to further investigate the association of tinnitus with depressive mood and/or suicidal ideation, and explore the shared risk factors for these within a representative sample of the adult general population. We also investigated potential mediation pathways among tinnitus, suicidal ideation, depression, shared risk factors, and perceived stress levels. We analysed data from 28, 930 adults (aged ≥19 years) from the fourth and fifth Korea National Health and Nutrition Examination Surveys (KNHANES) conducted from 2008 to 2012 in South Korea. We investigated the presence and severity of tinnitus, depressive mood, suicidal ideation, perceived usual stress level, and socioeconomic and health-related variables. We conducted logistic regression and mediation analyses. Tinnitus and its severity were significantly associated with depressive mood and suicidal ideation. Tinnitus, depressive mood, and suicidal ideation shared common socioeconomic and health-related risk factors. Tinnitus significantly mediated the association of shared risk factors for depressive mood and suicidal ideation. Perceived usual stress level mediates the association of tinnitus with depressive mood and suicidal ideation. The correlation of perceived usual stress levels with depression and suicidal ideation was also mediated by tinnitus. Our findings implicate that tinnitus may contribute substantially to the development of depressive symptom and suicidal ideation in adults via apparent interactions with shared risk factors and stress levels. Highlights: A nationally representative sample of 28, 930 adults aged 19 years old or above. Significant association of tinnitus with depression and suicidal ideation. Tinnitus mediated association of shared risk factors for depression/suicidal thought. Stress level mediated association of tinnitus with depression/suicidal thought.